2013
DOI: 10.1189/jlb.0813462
|View full text |Cite
|
Sign up to set email alerts
|

DAPK2 positively regulates motility of neutrophils and eosinophils in response to intermediary chemoattractants

Abstract: The tight regulation of granulocyte chemotaxis is crucial for initiation and resolution of inflammation. Here, we show that DAPK2, a Ca(2+)/CaM-sensitive serine/threonine kinase known to modulate cell death in various cell types, is a novel regulator of migration in granulocytes. We demonstrate that human neutrophils and eosinophils express DAPK2 but unlike other leukocytes, no DAPK1 or DAPK3 protein. When DAPK activities were blocked by inhibitors, we found that neither granulocyte lifespan nor phagocytosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
(57 reference statements)
4
27
0
Order By: Relevance
“…S4 in the supplemental material). Quantification of the changes in cell-free area over time revealed that ectopic expression of two complementary split YFP-DAPK2 constructs (YFP N -DAPK2 and YFP C -DAPK2), leading to DAPK2 homodimerization, indeed resulted in cells with increased migration compared to levels in cells expressing control constructs, in line with previous reports that inhibition of DAPK2 activity slows down cellular motility (17). Expression of split YFP-DAPK2 and -CaM or -␣-actinin-1, however, caused the cells to move more slowly, resulting in reduced closure of the wound.…”
Section: Unbiased Identification Of Potential Dapk2 Interaction Partnsupporting
confidence: 64%
See 4 more Smart Citations
“…S4 in the supplemental material). Quantification of the changes in cell-free area over time revealed that ectopic expression of two complementary split YFP-DAPK2 constructs (YFP N -DAPK2 and YFP C -DAPK2), leading to DAPK2 homodimerization, indeed resulted in cells with increased migration compared to levels in cells expressing control constructs, in line with previous reports that inhibition of DAPK2 activity slows down cellular motility (17). Expression of split YFP-DAPK2 and -CaM or -␣-actinin-1, however, caused the cells to move more slowly, resulting in reduced closure of the wound.…”
Section: Unbiased Identification Of Potential Dapk2 Interaction Partnsupporting
confidence: 64%
“…Whereas DAPK1 negatively regulates migration of cells by interfering with integrin signaling (30), DAPK2 positively regulates migration by acting on spreading and polarization (17). Here, we used a scratch assay to investigate whether DAPK2 homodimerization or its interaction with CaM, ␣-actinin-1, or 14-3-3-␤ would have an impact on cellular migration.…”
Section: Unbiased Identification Of Potential Dapk2 Interaction Partnmentioning
confidence: 99%
See 3 more Smart Citations